(untitled) (Intercom - Brazilian Journal of Communication Sciences, 2025)
This research analyzes the results of the implementation of 15 community health communication initiatives that received international support during pandemia. The qualitative and descriptive study had data collection via participant observation and documentary research in the reports presented periodically by each project in the five Brazilian regions. Through content analysis, their network of local partners was expanded, and most of the initiatives had local sources and addressed community problems, with the participation of community members in a networked communication model, paying attention to the sustainability of the actions with the end of financing. The creation of a network community between communicators and Oswaldo Cruz Foundation and Panamerican Health Organization was strengthened, as well as the possibility of multiplying solutions in community communication in health emergencies and their consequences.